Chemical imaging of coal in micro-scale with Raman mapping technology. (15th March 2020) - Xu, Jun; Liu, Jiawei; Zhang, Xin; Ling, Peng; Xu, Kai; He, Limo; Su, Sheng; Wang, Yi; Hu, Song; Xiang, Jun
Graphical abstract: Highlights: Chemical structures of three two-dimensional coal planes were investigated. The results of Raman mapping and petrography analysis were in-situ coupled. Good self-correlations between Raman spectral parameters were found. Coal macerals show different chemical structure characteristics in micro-scale. High resolution chemical imaging of coal in micro-scale was realized. Abstract: Raman mapping and petrography analysis of three two-dimensional planes including typical coal macerals in a lignite were done and coupled. The self-correlations between Raman spectral parameters and the relationship between Raman spectral parameters and random reflectivity (Rf ) of coal maceral particles were set up. The results indicate that the area ratio of D band to G band (AD /AG ) and intensity ratio of D band to G band (ID /IG ) should not be equal, and they were not well related to Rf of coal maceral particles. Good self-correlations between full width at half maximum intensity of G band (G FWHM), the total area of first-order Raman spectrum (SAll ) and fluorescence interference degree defined as drift coefficient α were found. G FWHM, SAll and α are also well related to Rf and can act as good indicators for chemical structure characteristics of coal maceral particles. With the increase of Rf, the relative amount of polyolefin, small aromatic rings, C–H, C-O, O–H etc. substitutional groups in vitrinite and liptinite decreases drastically, while the increase of aromatic ring size mainly takes place in inertinite. Chemical imaging of two-dimensional coal planes at a very high resolution was realized by drift coefficient α, and reproduction of the distribution of coal macerals in micro-scale is reasonable. The Raman mapping technology developed can be further used to deeply study the chemical structures of detailed coal macerals. This study can be further extended for rapid identification and detection of coal macerals by micro-Raman spectroscopy.